THE MYCOBIOTA OAK FORESTS OF THE URAL RIVER VALLEY WITHIN THE WEST KAZAKHSTAN REGION (Experimental biology, 2022)
The study and conservation of biodiversity is one of the global problems of modern biology, since at present in many regions of the planet there is a decrease in the species composition of various organisms, including fungi. The information obtained makes a significant contribution to the knowledge of the diversity of macromycetes of oak forests in the middle reaches of the Ural River, information about which in Kazakhstan is still insufficient and fragmented.The article presents data on the biodiversity of the mycobiota of oak forests of the Urals valley, growing not only in the floodplain of the river, but also in beams, that is, the ravine forests flowing into the central floodplain. We have registered 31 species belonging to 23 genera, 17 families and five orders. The leading families are Polyporaceae, Boletaceae, Russulaceae, Amanitaceae. As a result of our research, it has been found that the mycological composition in ravine oak forests is richer than in floodplain oak forests. The richness of the species composition of macromycetes appears to have been influenced by well-defined associations in ravine oak forests (22 associations), represented by forest boreal tree-shrub species absent in floodplain oak forests, as well as favorable microclimatic conditions, relief, soil cover and various ecotopes that are not observed in floodplain oak forests (16 associations).Ecological-trophic analysis showed a predominance of mycorrhizal (45.1%) and xylotrophs (41.9%) over humus saprotrophs (12.9%). The considered taxonomic composition of macromycetes of the studied area is collected, identified and presented for the first time for this region.Key words: mycobiota, macromycetes, oak forest, Ural river, biodiversity.
Keywords: : mycobiota, macromycetes, oak forest, Ural river, biodiversity.